2020
DOI: 10.14710/tataloka.22.4.556-572
|View full text |Cite
|
Sign up to set email alerts
|

Cakupan Kesehatan Universal (UHC) Pekerja Sektor Informal di Indonesia

Abstract: Health insurance receives a great deal of attention in the SDG’s, where one of its main targets is to guarantee a healthy life and to encourage welfare for all people of all ages or later to be called Universal Health Coverage (UHC). In Indonesia there are more informal workers than formal sector workers, but almost half of informal sector workers work without health insurance protection. This study aims to determine the achievement of UHC in terms of ownership of health insurance for informal sector workers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
1
0
5

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 5 publications
1
1
0
5
Order By: Relevance
“…The primary school variable has a significant influence on economic growth in only 4 provinces in Indonesia such as DKI Jakarta (0.0000), West Java (0.0000), Central Java (0.0010) and East Java (0.0000) and in 30 other provinces have no significant effect. This is in line with research (Satriawan et al, 2020) that most informal sector workers in Indonesia are poorly educated. The largest percentage, namely at the basic education level (not graduating from elementary school and never going to school) reached 52.13%.…”
Section: Methodssupporting
confidence: 91%
“…The primary school variable has a significant influence on economic growth in only 4 provinces in Indonesia such as DKI Jakarta (0.0000), West Java (0.0000), Central Java (0.0010) and East Java (0.0000) and in 30 other provinces have no significant effect. This is in line with research (Satriawan et al, 2020) that most informal sector workers in Indonesia are poorly educated. The largest percentage, namely at the basic education level (not graduating from elementary school and never going to school) reached 52.13%.…”
Section: Methodssupporting
confidence: 91%
“…Therefore, it can be concluded that people who take longer education are believed to have higher skill levels, are knowledgeable, and are more productive in the future (Ince, 2010). Through education, informal sector workers can change their status as formal sector workers (Satriawan, Pitoyo, & Giyarsih, 2020), considering that informal sector workers are still far from being based on social security and good health.…”
Section: Discussionmentioning
confidence: 99%
“…Pada Tahun 2017 Survei Angkatan Kerja Nasional (SAKERNAS) menyebutkan jumlah pekerja sektor informal di Indonesia mencapai 57,03% dari total penduduk yang bekerja secara nasional [2]. Sektor informal dapat menjadi strategi bertahan hidup yang dikenal oleh masyarakat terutama masyarakat menengah ke bawah [2].…”
Section: Pendahuluanunclassified
“…Pada Tahun 2017 Survei Angkatan Kerja Nasional (SAKERNAS) menyebutkan jumlah pekerja sektor informal di Indonesia mencapai 57,03% dari total penduduk yang bekerja secara nasional [2]. Sektor informal dapat menjadi strategi bertahan hidup yang dikenal oleh masyarakat terutama masyarakat menengah ke bawah [2]. Banyaknya jumlah pekerja di sektor informal dan kontribusi yang nyata dalam pembangunan, menjadi alasan kuat untuk pemerintah dalam menjamin perlindungan bagi pekerja [3].…”
Section: Pendahuluanunclassified
See 1 more Smart Citation